∫ 0 1 − ln x d x ∫ 0 1 − ln x d x ∫ 0 1 1 + x 2 ln 2 x d x ∫ 0 ∞ 1 + x 2 ln x d x ∫ 0 ∞ 1 + x 3 ln x d x ∫ − 1 1 e x 1 + 1 cos x d x ∫ 0 ∞ x 2 sin 3 x d x ∫ 0 ∞ ( x sin x ) 5 d x ∫ 0 ∞ ( x sin x ) 6 d x = A π = B π = D π C = E = − F B π B = sin A = G C ln C = I H π = K J π
Here, A , B , C , D , E , F , G , H , I , J , K are distinct positive integers and all the fractions are in their simplest forms.
Find A + B + C + D + E + F + G + H + I + J + K
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please complete the solution. Been waiting a long time.
Log in to reply
The rest are very long.
I have given all the answers. The solutions are simply too long.
Problem Loading...
Note Loading...
Set Loading...
∫ 0 1 − ln x d x = ∫ 0 1 ln x 1 d x = − ∫ ∞ 1 u 2 ln u d u = ∫ 0 ∞ t 2 1 − 1 e − t d t = Γ ( 2 1 ) = π Let u = x 1 ⟹ d u = − x 2 d x Let t = ln u ⟹ e t d t = d u where Γ ( ⋅ ) denotes the gamma function.
⟹ A = 1
∫ 0 1 − ln x d x = ∫ 0 1 ln x 1 d x = − ∫ ∞ 1 u 2 ln u d u = ∫ 0 ∞ t 2 3 − 1 e − t d t = Γ ( 2 3 ) = 2 1 Γ ( 2 1 ) = 2 π Let u = x 1 ⟹ d u = − x 2 d x Let t = ln u ⟹ e t d t = d u
⟹ B = 2
∫ 0 1 1 + x 2 ln 2 x d x = ∫ 0 1 ( x − i ) ( x + i ) ln 2 x d x = ∫ 0 1 ( 2 ( x + i ) i ln 2 x − 2 ( x − i ) i ln 2 x ) d x = 2 i ( ∫ i 1 + i u ln 2 ( u − i ) d u − ∫ − i 1 − i v ln 2 ( v + i ) d v ) = 2 i ( ln ( − i u ) ln 2 ( u − i ) ∣ ∣ ∣ ∣ i 1 + i 0 − 2 ∫ i 1 + i u − i ln ( − i u ) ln ( u − i ) d u − ln ( i v ) ln 2 ( v + i ) ∣ ∣ ∣ ∣ − i 1 − i 0 + 2 ∫ − i 1 − i v + i ln ( i v ) ln ( v + i ) d v ) = i ( − ∫ i 1 + i u − i ln ( − i u ) ln ( u − i ) d u + ∫ − i 1 − i v + i ln ( i v ) ln ( v + i ) d v ) = i ( ln ( u − i ) Li 2 ( i u + 1 ) ∣ ∣ ∣ ∣ i 1 + i 0 − ∫ i 1 + i ln ( u − i ) Li 2 ( i u + 1 ) d u − ln ( v + i ) Li 2 ( 1 − i v ) ∣ ∣ ∣ ∣ − i 1 − i 0 + ∫ − i 1 − i ln ( v + i ) Li 2 ( 1 − i v ) d v ) = i ( − ∫ i 1 + i ln ( u − i ) Li 2 ( i u + 1 ) d u + ∫ − i 1 − i ln ( v + i ) Li 2 ( 1 − i v ) d v ) = i ( − Li 3 ( i u + 1 ) ∣ ∣ ∣ ∣ i 1 + i + Li 3 ( 1 − i v ) ∣ ∣ ∣ ∣ − i 1 − i ) = i ( − Li 3 ( i ) + Li 3 ( 0 ) + Li 3 ( − i ) − Li 3 ( 0 ) ) = 1 6 π 3 By partial fraction Let u = x + i , v = x − i By integration by parts By integration by parts Li s ( z ) is polylogarithm function.
⟹ C = 3 and D = 1 6
∫ 0 ∞ 1 + x 2 ln x d x = 2 1 ∫ 0 ∞ ( 1 + x 2 ln x + x 2 ( 1 + x 2 1 ) ln x 1 ) d x = 2 1 ∫ 0 ∞ ( 1 + x 2 ln x − x 2 + 1 ln x ) d x = 0 Using ∫ 0 ∞ f ( x ) d x = ∫ 0 ∞ x 2 f ( x 1 ) d x
⟹ E = 0
Solution too tedius to show
∫ 0 ∞ 1 + x 3 ln x d x = ∫ 0 ∞ ( x + 1 ) ( x 2 − x + 1 ) ln x d x = − 2 7 2 π 2
⟹ F = 2 7
∫ − 1 1 e x 1 + 1 cos x d x = 2 1 ∫ − 1 1 ( e x 1 + 1 cos x + e − x 1 + 1 cos ( − x ) ) d x = ∫ − 1 1 ( e x 1 + 1 cos x + 1 + e x 1 e x 1 cos x ) d x = 2 1 ∫ − 1 1 cos x d x = 2 1 sin x ∣ ∣ ∣ ∣ − 1 1 = sin 1 Using ∫ a b f ( x ) d x = 2 1 ∫ a b f ( a + b − x ) d x
∫ 0 ∞ x 2 sin 3 x d x = 4 3 ∫ 0 ∞ x 2 sin x d x − 4 1 ∫ 0 ∞ x 2 sin 3 x d x = − 4 x 3 sin x ∣ ∣ ∣ ∣ 0 ∞ + 4 3 ∫ 0 ∞ x cos x d x + 4 x sin 3 x ∣ ∣ ∣ ∣ 0 ∞ − 4 1 ∫ 0 ∞ x 3 cos 3 x d x = − 4 3 + x → 0 lim 4 3 Ci ( x ) + 4 3 − x → 0 lim 4 3 Ci ( 3 x ) = 4 3 x → 0 lim ( Ci ( x ) − Ci ( 3 x ) ) = 4 3 ln 3 Using sin 3 θ = 3 sin θ − 4 sin 3 θ By integration by parts
⟹ G = 4
Solution too tedius to show
∫ 0 ∞ x 5 sin 5 x d x = ∫ 0 ∞ 1 6 x 5 sin 5 x − 5 sin 3 x + 1 0 sin x d x = 3 8 4 1 1 5 π
⟹ H = 1 1 5 and I = 3 8 4
Solution too tedius to show
∫ 0 ∞ x 6 sin 6 x d x = ∫ 0 ∞ 3 2 x 5 1 0 − 1 5 cos 2 x + 6 cos 4 x − cos 6 x d x = 4 0 1 1 π
⟹ J = 1 1 and K = 4 0
⟹ A + B + C + D + E + F + G + H + I + J + K = 1 + 2 + 3 + 1 6 + 0 + 2 7 + 4 + 1 1 5 + 3 8 4 + 1 1 + 4 0 = 6 0 3